Ensifer-mediated transformation: an efficient non-Agrobacterium protocol for the genetic modification of rice - Zuñiga-Soto, Evelyn; Mullins, Ewen; Dedicova, Beata (Springer, 2015)
While Agrobacterium-mediated transformation (AMT) remains the most widely used technique for gene transfer in plants, interest exists for the use of non-Agrobacterium gene delivery systems due to freedom-to-operate issues that remain with AMT across several jurisdictions. In addition, the plant pathogenic mode of action of Agrobacterium tumefaciens significantly increases the costs to passage engineered cultivars through the regulatory process. Ensifer adhaerens (OV14) is a soil-related bacterium with the proven ability to genetically modify the model plant A. thaliana and the staple crop S. tuberosum (Wendt et al., Trans Res 21:567-578, 2012). While previous work was relevant for dicotyledonous species, in this study, the efficacy of Ensifer adhaerens (OV14)-mediated transformation (EMT) was determined on two japonica rice varieties, Curinga and Nipponbare, and the recalcitrant indica variety, IR64. The results indicated that E. adhaerens (OV14) exhibits infection efficiencies ranging between 50-70 %, 90-100 % and 90-95 % for Curinga, Nipponbare and IR64 respectively. Curinga and Nipponbare plants transformed with E. adhaerens (OV14) and A. tumefaciens (LBA4404 and EHA105) were regenerated achieving transformation efficiencies of 16 % and 26-32 % for Curinga and 7 and 4 % for Nipponbare respectively. Separately, the transformation of IR64 was only recorded via EMT (transformation efficiency ~1 %). Integration analyses conducted on 24 transgenic rice lines illustrated that T-DNA insertion occurred randomly throughout the rice genome for EMT (and AMT), with similar integration patterns in the rice genomic DNA observed for both bacterial species.